1997
DOI: 10.1002/hep.510250428
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide induces hepatocyte cell death through disruption of mitochondrial function in the rat

Abstract: known to induce hepatocellular injury. 5,6 Although ceramides Although ceramide signaling pathways have been imare well known to cause cell death by inducing apoptosis, plicated in cell death, neither their role in hepatocellular they can also cause cell death by necrosis. [3][4][5]7 Based on these death nor the cellular mechanisms mediating ceramidedata, we generated the hypothesis that the ceramide signalinduced cell death are known. The mitochondrial meming pathway induces cell death in hepatocytes, either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
104
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(112 citation statements)
references
References 23 publications
1
104
3
Order By: Relevance
“…Thus, Bcl-xL appears to account for at least a portion of sIg-induced Fas-resistance because, expression was upregulated coordinately with induction of Fas-resistance (in both murine and human B cells, reference [69]), and, because isolated overexpression diminished B cell susceptibility to Fas killing separate and apart from any other potential effects of sIg engagement (although in connection with this last point it should be mentioned that the capacity of Bcl-xL to inhibit Fas-mediated apoptosis in B cell lines has been questioned, reference [70]). Further, the reduction in susceptibility to Th1-induced cytotoxicity produced by Bcl-xL suggests that Fas death signaling in B cells involves mitochondrial cytochrome c release; this notion is supported by our observation that inducibly Fas-resistant B cells are protected against apoptosis produced by C2-ceramide, the cytotoxicity of which has been associated with mitochondrial damage [71][72][73][74][75][ [71][72][73][74][75].…”
Section: Two Terminal Effectors Of Fas-resistance: Bcl-xl and Flipmentioning
confidence: 52%
“…Thus, Bcl-xL appears to account for at least a portion of sIg-induced Fas-resistance because, expression was upregulated coordinately with induction of Fas-resistance (in both murine and human B cells, reference [69]), and, because isolated overexpression diminished B cell susceptibility to Fas killing separate and apart from any other potential effects of sIg engagement (although in connection with this last point it should be mentioned that the capacity of Bcl-xL to inhibit Fas-mediated apoptosis in B cell lines has been questioned, reference [70]). Further, the reduction in susceptibility to Th1-induced cytotoxicity produced by Bcl-xL suggests that Fas death signaling in B cells involves mitochondrial cytochrome c release; this notion is supported by our observation that inducibly Fas-resistant B cells are protected against apoptosis produced by C2-ceramide, the cytotoxicity of which has been associated with mitochondrial damage [71][72][73][74][75][ [71][72][73][74][75].…”
Section: Two Terminal Effectors Of Fas-resistance: Bcl-xl and Flipmentioning
confidence: 52%
“…In this regard, it has been recently reported that cell-permeable ceramide analogues elicit a direct effect on mitochondria ranging from ROS overproduction, inhibition of respiratory complex III, and induction of mitochondrial permeability transition. 18,[47][48][49] Thus, our findings raise the intriguing possibility that the fate of endogenous ceramide in targeting mitochondria may depend on the cellular site where ceramide is released. Although the exact cellular location of ceramide generation by bSMase and hSMase is not known, 9.…”
Section: Discussionmentioning
confidence: 79%
“…Previous studies have shown that cell-permeable ceramide analogues induce necrosis in hepatocytes in suspension 49 or apoptosis in cultured hepatocytes only upon blocking RNA synthesis or nuclear factor-B inactivation. 53 Our work, however, analyzed the role of natural ceramides generated by distinct SMases on the survival of cultured rat hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that ceramide has a direct proapoptotic effect on the mitochondrial cascade. 7,8,25 Overall, these findings led us to investigate the involvement of BEX2 in the mitochondrial apoptosis pathway.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10]25 To investigate this we first carried out a mitochondrial permeability transition (MPT)-based apoptosis assay, which detects changes in…”
Section: Bex2 Protects the Breast Cancer Cells Against Mitochondrial mentioning
confidence: 99%